Application of Augmented Reality (AR) in T-Shirt Catalog (International Journal of Innovative Computing, 2019)
Augmented Reality (AR) is a visual technology that able to provide users with a semi-real time experience. The advancement of mobile phone and camera technology have make the potential of AR emerged. Companies wants high product sales and look more advanced than their competitors. One of the effort is to provide customers with correct experience of their products. Catalog is a tool to market a product. However, paper printing catalog is two dimensional, and has limitation in fully presenting the product. This work, presents the adoption of AR in T-shirt catalog. The application utilized Android mobile phone to view the 3D model of the t-shirt. The user scan the catalog using the android handphone on the paper printing catalog, and they able to view in 3D the different angle of the T-shirt. This application has successfully developed and testing has been made on compatibility and functionality test.
Keywords: AR; Augmented Reality; Marker base; Marker-less based; Catalog; Android; mobile application; advertising